The Causal Effect of Education on Health: What is the Role of Health Behaviors? - Giorgio Brunello; Margherita Fort; Nicole Schneeweis; Rudolf Winter-Ebmer (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We study the contribution of health-related behaviors to the health education gradient by distinguishing between short-run and long-run mediating effects: while in the former only behaviors in the immediate past are taken into account, in the latter we consider the entire history of behaviors. We use an empirical approach that addresses the endogeneity of education and behaviors in the health production function. Focusing on self-reported poor health, we find that education has a protective effect for European males and females aged 50. We also find that the mediating effects of health behaviors - measured by smoking, drinking, exercising and the body mass index - account in the short-run for 17% to 31% and in the long-run for 23% to 45% of the entire effect of education on health, depending on gender.
Keywords: J1; I12; I21; 330